Impacts of Mobile Phones on Children's Academic Performance: A Study in Institutional School, Birendranagar, Surkhet (Spectrum of Humanities and Social Sciences, 2025)
This study examines the impacts of mobile phone use on children's academic performance at an institutional school in Surkhet. Using a descriptive research design with purposive sampling, data were collected from 47 students. Findings show that the majority of students have own mobile phone and recognize their educational benefits. However, many students admitted that their usage often distracted students from academic tasks. A large proportion of parents and teachers expressed concerns that mobile phones negatively impact students' concentration, with many believing they hinder academic performance. Despite these drawbacks, a majority recognized mobile phones as valuable educational tools, though an equal percentage observed a decline in face-to-face interactions due to mobile usage. Furthermore, a considerable number of respondents identified excessive mobile phone use among students, and a significant portion reported signs of mobile addiction. These findings highlight the dual impact of mobile phones—while they serve as useful learning tools, they also pose challenges to academic performance and social engagement. The study underscores the importance of a balanced approach to mobile phone use, ensuring that their educational advantages are maximized while minimizing potential distractions